Amyloid-beta-derived peptidomimetics inhibits tau aggregation - Gorantla, V. Nalini; Sunny, Lisni P.; Rajasekhar, Kolla; Nagaraju, Pramod G.; Priyadarshini, Poornima C. G.; Govindaraju, Thimmaiah; Chinnathambi, Subashchandrabose (ACS Omega, 2021)
The aggregation of tau protein is one of the hallmarks for Alzheimer's disease, resulting in neurodegeneration. The peptidomimetics strategy to prevent tau aggregation is more specific over other small molecules. In the present study, we analyzed the effect of amyloid-beta-derived peptidomimetics for inhibiting heparin-induced tau aggregation in vitro. These peptides and their derivatives were known to prevent aggregation of amyloid-beta. KLVFF is a hydrophobic sequence of the pentapeptide that prevented tau aggregation as observed by thioflavin S fluorescence, transmission electron microscopy, and circular dichroism spectroscopy. P4 and P5 also prevented assembly of tau into aggregates and formed short fibrils. The beta-sheet breaker LPFFD was however ineffective in preventing tau aggregation. The peptides further demonstrated reversal of tau-induced cytotoxicity in a dose-dependent manner. Our results suggested that these peptides can also be used to inhibit tau aggregation and also, toxicity induced by tau could be considered as potential molecules that have an effect on tau as well as amyloid-beta.

Influence of sodium caseinate, maltodextrin, pectin and their Maillard conjugate on the stability, in vitro release, anti-oxidant property and cell viability of eugenol-olive oil nanoemulsions - Nagaraju, Pramod G.; Sindhu, P.; Dubey, Tushar; Chinnathambi, Subashchandrabose; Priyadarshini, Poornima; Rao, Pooja J. (International Journal of Biological Macromolecules, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The influence of protein (sodium caseinate-SC), polysaccharide (maltodextrin-MD; pectin-PC) and their Maillard conjugates (sodium caseinate maltodextrin conjugate-SCMDC; sodium caseinate pectin conjugate-SCPCC) were studied on the physico-chemical and biological properties of eugenol nanoemulsions/powder. The chemical composition was optimized using Taguchi design. The particles size of eugenol nanoemulsions with SC, MD, PC, SCMDC and SCPCC were 104.6, 323.5, 1872, 181.7, and 454.4 nm, respectively while their zeta potentials were -31.2, -28.5, -21.4, -40.1 and -25.1 mV, respectively. Turbidity studies revealed higher stability of nanoemulsion prepared with Maillard conjugate (SCMDC) compared to protein or polysaccharides alone. The dispersion of SCMDC eugenol nanoparticles in buffer was prepared to study its stability at different pH (3.0, 5.0, and 7.0) and temperature (4°, 37°, 60 °C) range. In-vitro enzymatic release study showed 31 and 74% release of eugenol after 6 h at pH 2.4 and 7.4, respectively. In vitro antioxidant capacity of SCMDC encapsulated eugenol was higher than native eugenol, as demonstrated by free radical scavenging assays. In comparison to native eugenol, E:SCMDC eugenol showed reduced toxicity. These findings suggested that nanoencapsulated eugenol (E:SCMDC) have a huge potential in nutraceutical and therapeutic applications.